Noise exposures in different community settings measured by traditional dosimeter and smartphone app. (October 2020) - Jacobs, Neva; Roberts, Benjamin; Reamer, Heidi; Mathis, Claire; Gaffney, Shannon; Neitzel, Richard
Highlights: This paper evaluated the accuracy of the NIOSH SLM app in the general environment. Noise levels ranged between 42.6 dBA in offices and 101.7 dBA in spin classes. The average difference between the NIOSH app and dosimeters was less than 2.0 dBA. The app was most accurate when measuring noise > 75 dBA. Abstract: While occupational noise exposures are well understood in certain industries, increasing attention has recently been given to exposures in non-traditional and non-occupational settings. Further, there is growing interest in the use of smartphone sound level meter applications (apps) as an alternative to traditional noise measurement devices such as personal dosimeters. This research utilized a smartphone running the National Institute for Occupational Safety and Health (NIOSH) sound level meter app and a noise dosimeter to measure noise exposures in office, coffee shop, commuter train, restaurant, and spin class settings. Overall (N = 166), noise levels ranged from between 47.7 dBA and 42.6 dBA in the office setting to 101.2 dBA and 101.7 dBA in the spin class, for the smartphone and dosimeter, respectively. The mean difference in measurements was found to be less than 2.0 dBA (within the accuracy of typical noise measurement instruments) for measurements made in a commuter train, restaurant, and spin class locations. Our results suggest that the NIOSH app (without calibration or an external microphone) can be used as an effective screening tool in some settings, particularly when noise levels are stable and exceed 75 dBA. These results are especially timely as wearables (watches and fitness bands) begin to use internal microphones to measure sounds levels. These technologies may face similar measurement issues as we have identified for smartphones without an external calibrated microphone.